ANALISIS STRATEGI MARKETING POLITIK HARIS-SANI PADA PILKADA PROVINSI JAMBI TAHUN 2020 - Lia Syahfitri (2022)
Jambi Province is one of the regions that participated in the contestation. In its implementation. KPU determined three pairs of candidates consisting of: 1) Cek HendraRatu Munawaroh, 2) Fachrori Umar-Syafril Nursal, and 3) Al Haris-Abdullah Sani. The Jambi Provincial Pilkada was won by the Al Haris-Abdullah Sani pair with a narrow advantage over the Cek Hendra-Ratu Munawaroh pair by 08% or 12,148 votes. HarisSani's victory was not a predictable victory. Based on several survey results, it shows the lack of electability of this candidate pair. The problem that will be discussed in this research is how is Haris-Sani's political marketing strategy in the 2020 Jambi Provincial elections?. This study uses the Political Marketing theory of Adman Nursal where in this theory it is stated that there are three kinds of political marketing delivery processes that are useful for presenting political products that have been prepared, namely push marketing, pull marketing, and pass marketing. The method used is descriptive qualitative with primary and secondary data sources. The sampling technique was carried out by interview, documentation and observation techniques. The results of this study show that a good political product delivery process has been carried out by the Haris-Sani couple. Of course, this delivery process is based on a good political marketing strategy (segmentation, positioning, and targeting). So that political marketing carried out by Haris-Sani is able to increase the electability of candidates at election time.